Proton Conductance of Influenza Virus M2 Protein in Planar Lipid Bilayers - Vijayvergiya, Viksita (The Biophysical Society, 2004)
Purified M2 protein from the Udorn strain of influenza virus was reconstituted into planar lipid bilayers from liposomes. In 1 mM HCl, the single-channel conductance was measured as 6 pS with open probability of ≤0.03. The current voltage curve is linear over the achievable voltage range. The current amplitude is amantadine sensitive. In HCl solutions, the single-channel current was essentially invariant with changes in [Cl(−)], [Na(+)], and [tetraethylammonium] ([TEA(+)]), but dependent on [H(+)]. The reversal potential, determined with asymmetrical hydrogen chloride solution, is very close to the equilibrium potential of hydrogen. This appears to be the first report of single-channel proton currents with the full-length M2 protein.